Sumas y restas de la diplomacia y la cooperación cultural mexicana (1998-2008) - Cruz Vázquez, Eduardo (Revista Mexicana de Política Exterior, 2022)
There are many lessons to be learned from Mexico’s contribution to international cultural cooperation in the past, yet its future is uncertain. The current crisis could prove to be a smokescreen that prevents us from making the changes needed to bring about a fully-fledged form of cultural diplomacy. That said, according to Eduardo Cruz, debate on the bill for an International Cooperation Law on Matters of Development and the role a Mexican Agency for International Cooperation on Matters of Development would play is an opportunity to establish a model that more clearly outlines what Mexico can hope to obtain from such cooperation and what it can aspire to contribute in this area in the coming months and years.